Desain Media Pembelajaran Hyperlink Berbasis Canva pada Materi Asmaul Husna Kelas X - Arrasyid, Ihsan Auliya; Sidqi, Ansori (Lembaga Yasin AlSys, 2024)
This research aims to develop hyperlink-based learning media using Canva application on Asmaul Husna material for grade X students. This learning media is designed as an innovative solution that utilizes interactive features to increase student interest, understanding, and involvement in the learning process. The method used is Research and Development (R&D) with the 4-D development model (Define, Design, Develop, and Disseminate), although in this study only until the development stage. The validation results show that this media is very feasible to use, with a material expert eligibility score of 89.5%, and a media expert of 78.5%. So that the validation results obtained from the hyperlink feature on Canva on class X asmaul husna material can be used as one of the learning media that makes it easier for students to access various additional content such as videos and articles, thus creating a more dynamic and interactive learning experience.